Statistical analysis of planing hull motions and accelerations in irregular head sea. (15th January 2016) - Begovic, E.; Bertorello, C.; Pennino, S.; Piscopo, V.; Scamardella, A.
Abstract: The paper focuses on the analysis of experimental seakeeping data in irregular head sea relative to constant deadrise and warped model representative of current design trends for planing hull forms. Tests have been performed at four volumetric Froude numbers ranging from 2 to 4 in one sea state. Due to non-linear nature of high-speed craft dynamics, measured motions and accelerations have been statistically analysed with the aim to find the best-fit distributions. Obtained results for heave and pitch confirm that Rayleigh and Cartwright distributions can be applied with good confidence for statistical analysis of heights and maxima/minima respectively. Weibull distribution was found to be the best-fit for statistical analysis of vertical acceleration maxima at CG and bow. Finally, the mean of 1/3rd highest vertical accelerations for both models have been compared with Fridsma's data showing the covered range of velocities and sea states. The procedure for model-ship correlation is shown to make the results available in design practices. Highlights: Monohedral and warped models have been tested at four speeds in irregular head waves. Emphasis of work was on statistical analysis and best fit distribution. Reported results are heave, pitch, accelerations at midship and at bow. Comparison of mean of 1/3rd highest bow and CG accelerations with Fridsma's data is given. Results reported in this paper extend the range investigated.